2016
DOI: 10.1039/c6fd00026f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of the thermophysical properties and phase behaviour of impure CO2 relevant to CCS

Abstract: Impurities from the CCS chain can greatly influence the physical properties of CO 2 . This has important design, safety and cost implications for the compression, transport and storage of CO 2 . There is an urgent need to understand and predict the properties of impure CO 2 to assist with CCS implementation. However, CCS presents demanding modelling requirements. A suitable model must both accurately and robustly predict CO 2 phase behaviour over a wide range of temperature and pressure, and maintain that pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The force fields for Ar, N 2 , and O 2 were taken from the work of Vrabec et al These force fields were adjusted to experimental VLE data and it was shown that they are an adequate choice for numerous fluid mixtures. , For H 2 O, the widely appreciated TIP4P/2005 force field, which performs well for a large variety of thermodynamic properties, was employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force fields for Ar, N 2 , and O 2 were taken from the work of Vrabec et al These force fields were adjusted to experimental VLE data and it was shown that they are an adequate choice for numerous fluid mixtures. , For H 2 O, the widely appreciated TIP4P/2005 force field, which performs well for a large variety of thermodynamic properties, was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Several literature studies already dealt with some of these subsystems. Stoll et al and Vrabec et al performed molecular simulation studies on binary mixtures related to dry air (N 2 + O 2 , N 2 + Ar, and Ar + O 2 ), which were then used to predict cryogenic vapor–liquid equilibria (VLE) of dry air (N 2 + O 2 + Ar). , Furthermore, humid air (N 2 + O 2 + Ar + H 2 O) was examined by Eckl et al Related studies with a different objective, that is, CO 2 mixtures for carbon capture and sequestration (CCS) and the like, were conducted by means of molecular modeling and simulation by Vrabec et al (N 2 + O 2 + CO 2 ), Tenorio et al (H 2 + CO 2 ), and Cresswell et al (binary mixtures of CO 2 with H 2 , N 2 , Ar, and O 2 ). Moreover, several studies employed the statistical associating fluid theory (SAFT) in its various forms or cubic EOS to study mixtures containing CO 2 . , Solubilities of binary aqueous systems (N 2 + H 2 O and H 2 + H 2 O) were examined by Sun et al with the SAFT–Lennard-Jones EOS.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Latin hypercube (LHC) sampling, which is a space-filling design, has been employed to build data sets when modelling PESs with GPs [17][18][19]61 . The approach of Uteva et al 17 entailed designing LHCs in inverse separations over a range of angles that specified the symmetry-distinct region 17 .…”
Section: B Training Set Designmentioning
confidence: 99%
“…This approach proceeds by training a statistical technique on a relatively small set of data from ab initio calculations on the PES of interest, known as the training set. Many such techniques have been employed to predict the energy in these algorithms, including neural networks [9][10][11][12][13] , moment tensors [14][15][16] and Gaussian processes [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (GPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation